Penggunaan Media Wordwall sebagai Evaluasi Pembelajaran Organ Pernapasan pada Hewan Kelas V di SDN 3 Nagri Kaler - Primanita Sholihah Rosmana; Sofyan Iskandar; Adesti Novita Sari; Asthiyani Kholida; Dzulfa Nur Firdaus; Puput Trisnawati (Departement of Mathematics Education, 2023)
The background of this study was that there were students who felt lazy in working on some of the evaluation questions given by the teacher in science subjects regarding respiratory organs in animals. This is because the teacher still uses typed or handwritten evaluation questions on paper. Thus, the results obtained through evaluation are not optimal, because they do not attract students' interest and attention and are considered only mediocre. This study aims to utilize Wordwall media as a form of evaluation in Natural Sciences (IPA) subjects regarding respiratory organs in animals for class V students at SDN 3 Nagri Kaler. The research method used is Classroom Action Research which is designed in 2 cycles, each cycle consisting of 4 stages. Researchers in designing results and discussions discuss the use of the Wordwall website as digital media in evaluating learning regarding respiratory organ material in animals. In the discussion, the researcher also conducted tests in the form of pre-test and post-test to measure the extent of students' understanding of the material on respiratory organs in animals. Furthermore, at the end of the discussion, the researcher included data in the form of scores or results from the pre-test, post-test, and evaluation using Wordwall.